Liver transplantation alcohol related liver disease: (deliberately) stirring a hornet's nest! - O'Grady, J G (BMJ Group, 2006)
Outcomes after liver transplantation for alcohol related liver disease compare very favourably with those documented for other causes of cirrhosis. Despite this, 5% or less of patients with advanced alcohol related liver disease are considered for transplantation. The reasons for this are complex but include professional reluctance to refer these patients for formal assessment as well as a limited and dwindling number of organs available for transplantation. Demonstrating abstinence from alcohol consumption remains central to the assessment of candidates for transplantation. Return to alcohol consumption after transplantation can follow a pattern of abuse with consequences for health and survival but may also be controlled and of little clinical significance. A better understanding of the issues influencing these outcomes should decrease the tension that currently exists between patient expectations, professional opinion, and the attitude of the general public who gift organs for donation.